German Writers and Politics 1918–39
X, 225 p.
Keywords: Political changes between 1918 and 1939 had important implications for German writers. The essays in this volume focus on questions such as the writers' relationship to political parties and ideology, their treatment of the legacy of World War I, and their response to the rise of fascism.